The Impact of Information Technology Capability on Supply Chain Technology Adoption and Supply Chain Operational Performance: A Resource based View - Lee, Khai Loon; Nawanir, Gusman; Jalal, Hanaysha; Zahari, Abu Bakar (Science Publishing Corporation, 2018)
Organization increasingly relies on the supply chain technology to improve the supply chain operational performance. Yet, past evidence suggests that the adoption of supply chain technology does not guarantee enhanced supply chain operational performance. Drawing from the Resource Based View, this study found that information technology (IT) capability enabled supply chain technology adoption in achieving supply chain operational performance. Supply chain technology serves as a system in transforming IT capability into a higher value resources for an organization. The adoption of supply chain technology in managing supply chain deserved attention from researchers and practitioners, because business benefits from supply chain technology adoption improve firm’s supply chain performances which enhance reliability, improve responsiveness, increase agility, and minimize cost in operation functions. This study provides a unique theoretical framework intended to aid researchers and practitioners develop a more thorough understanding of the linkages between information technology capability, supply chain technology adoption, and supply chain operational performance. The total of 201 questionnaires were sent to Malaysia's textile and apparel company that is listed in the Federation of Malaysian Manufacturers (FMM) and Malaysian External Trade Development Corporation (MATRADE) directory. The total of 121 usable responses were obtained and analyzed through Partial Least Square Structural Equation Modeling (PLS-SEM). The discussion of this study is followed by presenting the results of the survey on the relationship of IT capability on supply chain technology adoption and supply chain operational performance. The results shown that supply chain technology adoption is mediating the relationship between IT capability and supply chain operation performance.